An Fuzzy Trust Based Energy Aware Multipath Secure Data Collection in WSN - Chitti Babu, Y; Anuradha, Ch; Sri Rama Chandra Murty, P (International Journal of Engineering and Technology, 2018)
A Wireless Sensor Network (WSN) is an array of radar nodules that energetically organize itself into a cable-less grid without utilizing any prevailing arrangement. One of the significant issues in WSNs is the driveâ€™s intake, whereby the gridâ€™s lifespan is reliant on this aspect. Security is another significant issues in cable-less radar grids, because of absence of wire/cable besides resource constraintâ€™s nature. Reliance model shows a key role in fortifying the radar grids by recognizing the egotistical, malevolent and give-in nodules and separating them from message grid. Directed Random Propagation (DRP) operates two-hop vicinity data to enhance the circulation competence, leading to a reduced pack capture possibility. In this study, Shuffled Frog Leaping Algorithm (SFLA) is applied to augment ill-defined faith centered drive conscious multiple route locked data group in WSN.Â Â